Tissue Engineering for the Temporomandibular Joint. Issue 2 (17th December 2018) - Acri, Timothy M.; Shin, Kyungsup; Seol, Dongrim; Laird, Noah Z.; Song, Ino; Geary, Sean M.; Chakka, Jaidev L.; Martin, James A.; Salem, Aliasger K.
Abstract: Tissue engineering potentially offers new treatments for disorders of the temporomandibular joint which frequently afflict patients. Damage or disease in this area adversely affects masticatory function and speaking, reducing patients' quality of life. Effective treatment options for patients suffering from severe temporomandibular joint disorders are in high demand because surgical options are restricted to removal of damaged tissue or complete replacement of the joint with prosthetics. Tissue engineering approaches for the temporomandibular joint are a promising alternative to the limited clinical treatment options. However, tissue engineering is still a developing field and only in its formative years for the temporomandibular joint. This review outlines the anatomical and physiological characteristics of the temporomandibular joint, clinical management of temporomandibular joint disorder, and current perspectives in the tissue engineering approach for the temporomandibular joint disorder. The tissue engineering perspectives have been categorized according to the primary structures of the temporomandibular joint: the disc, the mandibular condyle, and the glenoid fossa. In each section, contemporary approaches in cellularization, growth factor selection, and scaffold fabrication strategies are reviewed in detail along with their achievements and challenges. Abstract : This review describes tissue engineering approaches for the condyle, the articular disc, and the glenoid fossa/articular eminence of the temporomandibular joint. The purpose of this review is to provide a comprehensive summary and analysis of therapeutic approaches used for temporomandibular joint regeneration that includes cellular, growth factor, and scaffold‐based strategies.